(untitled) (Revista Ingesta, 2020)
The aim of this study was to identify ethical, health, culture and lifestyle elements involved in opting for vegetarianism, as well as the greatest difficulties encountered by vegetarians in their daily eating practices. Data were collected through electronic survey and focus group. In addition to identification processes, topics related to cultures, sociability, food, vegetarianism, health and well-being were addressed. Two hundred and two people with good levels of education, mostly of the middle classes, answered the survey. Most responses indicated that they had a good diet, adequate weight, a healthy lifestyle and that their health and well-being improved after adopting vegetarianism. Adherence to vegetarianism occurred mainly for ethical reasons related to animal rights. The greatest difficulties resulting from the choice for vegetarianism, in terms of sociability, were due to the family environment and the lack of options in restaurants. A focus group contributed to deepen the themes. The answers suggest that the choice for vegetarianism goes beyond food and impacts on social relationships, consumption and lifestyle, taking on a political dimension that can be called food activism, as it challenges the forms of power and dialogues with new forms of interaction between individuals, society, other living beings and the environment.